Uptake of cervical cancer screening and its associated factors among women of reproductive age in Kericho County - Joel Wanzala; Calvince Otieno Anino (PLoS ONE, 2026)
Cervical cancer is a public health issue among reproductive-aged women worldwide. It is the second most common cancer among females and contributes to 12.9% of new cancer cases and 11.84% of all cancer deaths annually. Early detection and treatment can prevent and cure the disease. Screening among women has gained global attention since it’s a crucial step in early detection. This study investigated the level of uptake of cervical cancer screening and factors associated with the cervical cancer screening among women aged 18–49 years in Bureti Constituency, Kericho County. The study adopted an institution-based cross-sectional study design. The study used systematic random sampling technique to select 328 women aged 18–49 who attended maternal and child health clinic at Kapkatet Sub-County Hospital during study period. Data was collected using structured questionnaires, including sociodemographic, awareness and knowledge and screening uptake sections. The data was analyzed using SPSS version 26.0. Descriptive analyses were performed to all the variables. Binary logistic regression analyses were conducted to assess factors associated with cervical cancer screening. The uptake of cervical cancer screening was 16.2% (n = 53, 95% CI: 10.5–23.4). We found that being 34 years and above (aOR = 1.43, 95% CI: 1.11–2.52, p < 0.001), having a primary education (aOR = 3.20, 95% CI: 1.50–7.00, p = 0.003), being self-employed (aOR = 5.20, 95% CI: 2.40–10.70, p < 0.001), or unemployed (aOR =7.50, 95% CI: 2.45–25.00, p < 0.001), and having a family history of cervical cancer (aOR = 2.10, 95% CI: 0.80–6.00, p = 0.015) significantly increased the odds of screening uptake. In contrast, earning an income of Ksh. 2,001–5,000 (aOR = 0.38, 95% CI: 0.10–0.90, p = 0.016) or> Ksh. 10,000 (aOR = 0.15, 95% CI: 0.06–0.33, p < 0.001) significantly decreased the odds of screening. Additionally, poor knowledge on risk factors (aOR = 0.50, 95% CI: 0.28–0.65, p < 0.001), signs and symptoms (aOR = 0.40, 95% CI: 0.10–0.70, p < 0.001), and groups at risk (aOR = 0.35, 95% CI: 0.15–0.60, p < 0.001) were all associated with lower odds of screening. Uptake of cervical cancer screening was influenced by multiple factors including socio-demographics and economic factors, awareness, and knowledge related factors. Thus, there is urgent need for intensified health education to enhance awareness and knowledge of women on cervical cancer and its screening.